Cascade upgrading of γ-valerolactone to biofuels. Issue 32 (23rd March 2015) - Yan, Kai; Lafleur, Todd; Wu, Xu; Chai, Jiajue; Wu, Guosheng; Xie, Xianmei
Abstract : Cascade upgrading of γ-valerolactone (GVL), produced from renewable cellulosic biomass, with selective conversion to biofuels pentyl valerate (PV) and pentane in one pot using a bifunctional Pd/HY catalyst is described. Abstract : Cascade upgrading of γ-valerolactone (GVL), produced from renewable cellulosic biomass, with selective conversion to biofuels pentyl valerate (PV) and pentane in one pot using a bifunctional Pd/HY catalyst is described. Excellent catalytic performance (over 99% conversion of GVL, 60.6% yield of PV and 22.9% yield of pentane) was achieved in one step. These biofuels can be targeted for gasoline and jet fuel applications.